M8 Non-tuberculous mycobacteria testing in bronchiectasis in the UK: data from the EMBARC registry. (12th November 2019) - Finch, S; van der Laan, R; Crichton, M; Clifton, I; Gatheral, T; Walker, P; Haworth, C; Hill, A; Loebinger, M; Goeminne, P; Aliberti, S; Polverino, E; et al.
Abstract : Introduction: Non-tuberculous mycobacterial (NTM) infections are frequently observed in bronchiectasis patients. Guidelines recommend testing for NTM in this setting and especially when treating with long-term macrolides, due to a substantial risk for emergence of macrolide resistant infections when patients are exposed to macrolide monotherapy. This study aims to investigate NTM testing in the UK bronchiectasis population from the EMBARC registry. Methods: The EMBARC registry is an international prospective observational study of patients with CT-confirmed bronchiectasis. Patient data is entered at baseline and annual follow-up. One of the 30 participating countries is the UK and patient data was analyzed for NTM testing in the 9 level 1 regions of England, Scotland, Wales and Northern Ireland. Results: From the 16, 891 patients enrolled in the EMBARC registry between January 2015 and March 2019, Patients were 58% female and the median age was 68 years (interquartile range 58–75) with a similar and age distribution among regions. Nearly 30, 000 patient years of follow-up data were available. From the 6076 UK enrolled patients across 87 UK centres, 1047 (17.2%) were tested for NTM at least once and 8.2% of them had a positive NTM isolate. NTM testing varied substantially between the regions with the lowest testing rate in Northern Ireland (8.3%) and highest rate in Scotland (35.5%). Macrolides were prescribed for bronchiectasis treatment in 12–34% of the patients with the highest frequency in Northern Ireland but the average testing for NTM in this population was only 24.8% (highest testing frequency 60.9% in Scotland and lowest 7.5% in Yorkshire and Humber). Conclusions: Both ERS and BTS bronchiectasis guidelines recommend NTM testing in bronchiectasis but the testing was only performed in 17.2% of the UK patients enrolled in EMBARC. Less than a quarter of UK bronchiectasis patients initiated on macrolides are tested for NTM with a wide regional range for NTM testing (7.5–60.9%). Greater awareness of NTM testing recommendations is needed.